PENAKSIR RASIO UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SEDERHANA MENGGUNAKAN KOEFISIEN VARIASI DAN MEDIAN - Riski Rahmadani; Arisman Adnan; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses three ratio estimators for the population mean in simple randomsampling using coefficient of variation and median of an auxiliary variable, which is areview from the article of Subramani and Kumarapandiyan. All estimators are biased,then their mean square errors (MSE) are determined. Furthermore, the mean squareerrors are compared to show which estimator is the most efficient estimator. This paperreveals that the estimator using coefficient of variation and the median has the smallestmean square error (MSE).